Mental Health of Children Living in Foster Families in Rural Rwanda: The Role of HIV and the Family Environment - Nduwimana, Estella (AIDS Behav, 2017)
Fostering children is common in sub-Saharan Africa, but few studies examine these children’s mental health needs. This study investigated the impact of living in a foster family on the mental health of HIV-positive, HIV-affected and HIV-unaffected children (n = 681 aged 10–17) in rural Rwanda. Regression analyses assessed the impact of living in a foster family on mental health, parenting, and daily hardships; multiple mediation analyses assessed whether family factors mediated the association between foster status and mental health. HIV-positive children were eight times more likely to live in foster families than HIV-unaffected children. Being HIV-affected was predictive of depression and irritability symptoms after controlling for family factors. Controlling for HIV-status, foster children had more symptoms of depression, anxiety, and irritability than non-fostered children. Positive parenting fully mediated the association between foster status and mental health. Mental health and parenting interventions for foster children and HIV-affected children may improve child outcomes.